(untitled) (Mugda Medical College Journal, 2022)
A 38-year old female patient was admitted into the Department of Medicine of Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, with the complaints of abdominal distension and retrosternal burning sensation for last eight months. She also gave history of previous hospitalization for the same reason. She also had complaints of an episode of seizure two years back. However, she was treated as a case of peptic ulcer disease in her previous admission in the district hospital. On clinical examination, adenoma sebaceum were observed on her face; hepatomegaly, and bilateral mid- and lower-abdominal masses were also found. She was sent for radiological investigations in the Department of Radiology & Imaging of the same hospital. The ultrasonogram of the abdomen showed multiple echogenic space occupying lesions in the liver along with bilateral echogenic kidneys and mild ascites. CT scan of the abdomen revealed hepatic angiomyolipomas, bilateral grossly enlarged and distorted kidneys having multiple angiomyolipomas, and sclerotic foci in the scanned part of bones. Moreover, CT scan of brain revealed multiple subependymal calcified nodules along with multiple sclerotic foci in the scanned part of bones. Those features were consistent with tuberous sclerosis. The patient was kept admitted and treated accordingly. After obtaining a written informed consent, she was presented as a special case in clinical education. Mugda Med Coll J. 2022; 5(1): 50-53